2022
DOI: 10.24018/ejedu.2022.3.3.353
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Essay about Inclusion and the Role of Teachers in Building an Inclusive Education

Abstract: This article is a theoretical essay that revisits the concept of inclusive education and places teachers at the heart of the educational commitment of all schools, which means, quality education for all students. The teacher's knowledge, attitudes and values influence the building of a learning environment that facilitates a focus on the needs of each student, placing the student in the middle of the edification of an inclusive school. In this article, we will, on one hand, value the need for the teacher to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…Guru yang berhasil menjalankan tugasnya secara efektif tidak hanya memiliki pengetahuan akademis yang mendalam, tetapi juga sikap dasar yang mencerminkan dedikasi, empati, dan keterampilan interpersonal yang kuat. Sikap dasar seorang guru melibatkan kemampuan untuk memahami kebutuhan dan keunikan setiap siswa, menciptakan lingkungan belajar yang inklusif, serta memberikan dorongan dan motivasi yang dapat menginspirasi perkembangan potensi peserta didik (Alam & Mohanty, 2023;Ferreira, 2022;Ramzan et al, 2023). Keberadaan guru bukan sekadar sebagai pengajar, melainkan sebagai pembentuk karakter dan pemimpin yang dapat membimbing generasi muda menuju kesuksesan dan kemandirian.…”
Section: Pendahuluanunclassified
“…Guru yang berhasil menjalankan tugasnya secara efektif tidak hanya memiliki pengetahuan akademis yang mendalam, tetapi juga sikap dasar yang mencerminkan dedikasi, empati, dan keterampilan interpersonal yang kuat. Sikap dasar seorang guru melibatkan kemampuan untuk memahami kebutuhan dan keunikan setiap siswa, menciptakan lingkungan belajar yang inklusif, serta memberikan dorongan dan motivasi yang dapat menginspirasi perkembangan potensi peserta didik (Alam & Mohanty, 2023;Ferreira, 2022;Ramzan et al, 2023). Keberadaan guru bukan sekadar sebagai pengajar, melainkan sebagai pembentuk karakter dan pemimpin yang dapat membimbing generasi muda menuju kesuksesan dan kemandirian.…”
Section: Pendahuluanunclassified
“…A vision of equality, and this changed the paradigm". To accomplish this, it is suggested that teachers need to be well-organised, have expert skills, have well-established routines and be adaptable to ever-changing conditions in the regular classroom [51].…”
Section: Theme 3-legislation and Policies For Inclusionmentioning
confidence: 99%
“…All students with diverse learning needs have the right to access a complete and exciting education on the same basis as their peers. Catholic schools strive to empower learners by celebrating differences and providing educational opportunities aimed at eliminating discrimination and focusing on growth and progress for all [12]- [16]. In the application of diversity learning, the question that needs to be considered is whether teachers' pay attention to differences in various things from students, for example, in terms of language, culture, socioeconomics, learning styles, abilities, and others in designing learning scenarios.…”
Section: Scientific and Elemental 4cmentioning
confidence: 99%